Triggerless particle identification systems using FPGA - Güney, Veli Uğur. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2010., 2010)
As the beam energy and event rate in experimental particle physics setups increases, the acquisition and analysis of the data created at the experiments become more complex. In the beginning, counting the recorded events on a photo-plate by hand was enough. Then, computerized automated methods of event selection and of- ine analysis has been used. But in that kind of setup for every signal channel coming from a detector one needs to have some special purpose hardware to identify particles. We made a next generation digital Data AQuisition (DAQ) system specialised to analyse pulse-based signals to replace the traditional setup. It is a triggerless particle identi cation system which uses Field Programmable Gate Array (FPGA) technology. It takes digitized electrical pulse signals coming from a scintillator-PhotoMultiplier Tube (PMT) system due to incoming charged particles as input and calculates the best t parameters of a prede ned modeling function to the pulse. All of the calculations are done on a specialized FPGA chip in real-time -our part of this work- with a deadtimeless manner and only important pulse parameters are sent to the computer.
Keywords: Particles.; Field programmable gate arrays.; Data collection systems, Automatic.; Detectors.